A New Platinum-Based Prodrug Candidate for Chemotherapy and Its Synergistic Effect With Hadrontherapy: Novel Strategy to Treat Glioblastoma - Ferrari, Beatrice; Roda, Elisa; Priori, Erica Cecilia; De Luca, Fabrizio; Facoetti, Angelica; Ravera, Mauro; Brandalise, Federico; Locatelli, Carlo Alessandro; Rossi, Paola; Bottone, Maria Grazia (Frontiers in Neuroscience, 2021)
Glioblastoma (GBM) is the most common tumour of the Central Nervous System. Current therapies, often associated with severe side effects, are inefficacious to contrast the GBM relapsing forms. Trying to overcome these drawbacks, (OC-6-44)-acetatodiamminedichlorido(2-(2-propynyl)octanoato)platinum(IV), also called Pt(IV)Ac-POA, has been recently synthesised. This new prodrug bearing as axial ligand (2-propynyl)octanoic acid (POA), a histone deacetylase inhibitor, has a higher activity due to (i) high cellular accumulation by virtue of high lipophilicity and (ii) inhibition of histone deacetylase, which leads to increased exposure of nuclear DNA, permitting higher platination and promoting cancer cells death. In the present study we investigated the effects induced by the Pt(IV)Ac-POA and its potential antitumor activity in human U251 glioblastoma cell line, using a battery of complementary techniques i.e. flow cytometry, immunocytochemistry, TEM and western blotting analyses. In addition, the synergistic effect of Pt(IV)Ac-POA associated with the innovative oncological hadrontherapy with carbon ions was investigated, with the aim to identify the most efficient anticancer treatment combination. Our in vitro data demonstrated that Pt(IV)Ac-POA is able to induce cell death, through different pathways, at concentrations lower than those tested for other platinum analogues. In particular, an enduring Pt(IV)Ac-POA antitumor effect, persisting in long-term treatment, was demonstrated. Interestingly, this effect was further amplified by the combined exposure to carbon ion radiation. In conclusion, Pt(IV)Ac-POA represents a promising prodrug to be incorporated into the treatment regimen for GBM. Moreover, synergistic efficacy of the combined protocol using chemotherapeutic Pt(IV)Ac-POA followed by carbon ion radiation, may represent a promising approach, which may overcome some typical limitations of conventional therapeutic protocols for GBM treatment.